Tasawuf Nusantara : rangkaian mutiara sufi terkemuka - Sri Mulyati (Jakarta : Kencana, 2006)
On development of Sufism and biography of sufis in Indonesia
Daftar pustaka : p. [253]-255
Keywords: Sufism -- Indonesia; Mysticism -- Islam -- Indonesia; Sufis -- Indonesia -- Biography; Sufism -- Biography